2022
DOI: 10.3389/feduc.2022.991068
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perceived equity, job enrichment, and burnout among educators in Indian private universities on job satisfaction and the desire to quit

Abstract: The desire to quit converts into actual attrition if left unaddressed. Additionally, employees’ job satisfaction strongly influences their desire to stay or leave. Several individual and organizational factors affect job satisfaction levels, all of which must be thoroughly analyzed to curb both the desire to quit and attrition. The current study tests a model associating perceived equity, job enrichment, and burnout with job satisfaction and the desire to quit of educators employed in private universities in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…While the complete correlations between burnout and work performance subscales are presented below, it must be noted that of all the burnout subscales, there was a positive correlation between personal achievement and the work performance subscale such as personal accountability rs (98) = .26, service excellence rs (98) = .25, also professionalism and functional expertise are significant and positively correlated, rs (98) = .31, rs (98) = .30 respectively. The result somehow supports that there is a significant association between job satisfaction and sub-dimensions of burnout (Annamalai, 2022). The increase in personal achievement level will increase professionalism and functional expertise among UM tourism management graduates.…”
Section: Significant Relationship Between Burnout and Work Performancesupporting
confidence: 59%
“…While the complete correlations between burnout and work performance subscales are presented below, it must be noted that of all the burnout subscales, there was a positive correlation between personal achievement and the work performance subscale such as personal accountability rs (98) = .26, service excellence rs (98) = .25, also professionalism and functional expertise are significant and positively correlated, rs (98) = .31, rs (98) = .30 respectively. The result somehow supports that there is a significant association between job satisfaction and sub-dimensions of burnout (Annamalai, 2022). The increase in personal achievement level will increase professionalism and functional expertise among UM tourism management graduates.…”
Section: Significant Relationship Between Burnout and Work Performancesupporting
confidence: 59%
“…This suggests a strong correlation between perceptions of fairness and JS. Supporting this, Annamalai (2022), found that perceived equity positively influenced JS. Additionally, to reach this level of satisfaction, employees must feel completely safe at their university workplace.…”
Section: Discussionmentioning
confidence: 80%
“…The “Dissatisfied” level indicates that workers partially agree with aspects related to incentives for course participation, event attendance, and training programs. Providing employees with opportunities for personal and professional growth, such as skill development, career advancement, and challenging tasks, can influence JS (Annamalai, 2022; Moloantoa and Dorasamy, 2017). Desselle and Conklin (2010) regression model highlighted institutional and department chair support as significant determinants of JS.…”
Section: Discussionmentioning
confidence: 99%
“…The essence and specifics of using public-private partnerships in the modern economy, as well as specific experience of using this mechanism in education, are considered in the works Mitra (2020), Nayak (2019), Opawole and Jagboro (2018), Opawole et al (2019), andZhu et al (2019). The financial aspects of education management in the structure of the social and investment model of economic growth are studied in the works Abildaeva et al (2022), Annamalai (2022), Ashour et al (2019), Dobrosotskiy et al (2019), Ramaditya et al (2022), Sanz and López-Iñesta (2022), Wright and Horta (2018).…”
Section: Literature Reviewmentioning
confidence: 99%